4 - L’Université tunisienne : entre localisation et internationalisation - Najem Dhaher, (Journal of Higher Education in Africa, 2009)
Higher education in Tunisia has undergone in the past few years a lot of changes, both quantitatively and qualitatively. These developments are impacting unviersities at all levels. The pedagogical system can hardly keep up with the disturbing growth of the university population. The infrastructure is quickly submerged and research organisation is now called into question. The opening of Tunisia’s trade borders has sped up changes in the academic system which is already devalorized. Upgrading it disrupts habits and identities, which at times engenders domestic tensions. International cooperation is growing stronger while the university is being more and more open to private companies. There has been, since the early 1990s, a fast growing number of students scrambling for access to Tunisian universities, resulting in the adoption of reforms in the academic system, including the duplication of the academic space and a new form of its urban organisation in the city. The Tunisian university is now faced with the exigencies of not only democratisation, but also of its socio-economic usefulness. It is also confronted with the new challenges stemming from the growing unemployment rate among graduates. From a spatial standpoint and in the search for a territorial otherwise regional balance, which has been lacking until the late 1980s, there is a ongoing pattern which favours proximity to the university and the new development of strategies for investment in knowledge.